Chemical composition of ferromanganese nodules from the Pacific Ocean using X-ray fluorescence - D Pasho (PANGAEA, 2023)
Manganese nodules were retrieved during cruises of the Scripps Oceanographic Institution (SIO). Their chemical composition was determined using X-ray fluorescence.